Art work : on the creative life - Mann, Sally, 1951- (Abrams Press, an imprint of ABRAMS, 2025)
"The much-anticipated new book by artist and New York Times bestselling author Sally Mann about the challenges and transcendent pleasures of the creative process. Art Work, by photographer and writer Sally Mann, offers a spellbinding mix of wild and illuminating stories, practical (and some impractical) advice, and life lessons for artists and writers--or anyone interested in the creative path. Written in the same frank, fearless, and occasionally outrageous tone of her bestselling memoir, Hold Still, this new book reaffirms Mann as a unique and resonant voice for our times. Illustrated throughout with photographs, journal entries, and letters that bring immediacy and poignancy to the narrative, Art Work is full of thought-provoking insights about the hazards of early promise; the unpredictable role of luck; the value of work, work, work, and more hard work; the challenges of rejection and distraction; the importance of risk-taking; and the rewards of knowing why and when you say yes. In sparkling prose and thoughtfully juxtaposed visuals and ephemera, Art Work is a generous, provocative, and compulsively readable exploration of creativity by one of our most original thinkers"--